Phenomenological Skepticism Reconsidered: A Husserlian Answer to Dennett’s Challenge - Belt, Jaakko (Frontiers in Psychology, 2020)
There is a long-standing tradition of questioning the viability and scientificity of first-person methods. Husserlian reflective methodology, in particular, has been challenged on the basis of its perceived inability to meet the standards of objectivity and reliability, leading to what has been called “phenomenological scepticism” (Roy, 2007). In this article, I reassess this line of objection by outlining Daniel C. Dennett’s empirically driven scepticism and reconstructing his methodological arguments against Husserlian phenomenology. His ensuing phenomenological scepticism can be divided into strong scepticism and categorical and gradual versions of weak scepticism. Both strands of Dennett’s criticism are then countered by analyzing the key components of Husserl’s methodology of phenomenological reflection: epoché and transcendental reduction, intentional analysis, eidetic variation, and intersubjective validation. Laying out the basic features of phenomenological reflection serves two purposes. First, it undermines Dennett’s methodological arguments, which are based on the unfounded assumptions that Husserl is committed to introspection, methodological solipsism, the first-person-plural presumption, and the lone-wolf approach. Second, it shows how Husserl’s own methodology can alleviate the more justified empirical worries concerning overinterpretation, underdescription, and disagreement. Finally, I argue that gradual weak scepticism is the only plausible form of phenomenological scepticism and conclude that Husserlian methodology is well-equipped to combat it.